Complex Call with Different Messages in Bokermannohyla ibitiguara (Anura, Hylidae), a Gladiator Frog of the Brazilian Cerrado - Nali, Renato C. [UNESP]; Prado, Cynthia P. A. [UNESP] (Soc Study Amphibians Reptiles, 2014)
The Gladiator Frog, Bokermannohyla ibitiguara, is a hylid endemic to the Brazilian Cerrado with a complex call composed of long and short notes. We describe the influence of male size and temperature on call properties and investigate the social contexts of the different notes of the call through direct observations and playback experiments conducted in the field. The dominant frequency correlated negatively with male body size, whereas the duration of the long note correlated positively; there was no correlation between pulse rate and male body size. Air temperature correlated negatively with the duration of the long note and positively with pulse rate. Playback experiments with males indicated that they did not change the proportion of long to short notes in the presence of an intruder (= playback), but rather, they changed the short notes, which became longer, with a lower dominant frequency and more pulses with variable intervals. We interpreted this call as an aggressive call. Our results suggest that females may choose males based on dominant frequency and duration of the long note, traits that might be under sexual selection. Moreover, short notes appear to be the territorial component of the mixed call, and the aggressive call is a variation of this component.